Identification and functional demonstration of miRNAs in the fungus Cryptococcus neoformans. - Nan Jiang (Public Library of Science (PLoS), 2012)
microRNAs (miRNAs), endogenous posttranscriptional repressors by base-pairing of their cognate mRNAs in plants and animals, have mostly been thought lost in the kingdom of fungi. Here, we report the identification of miRNAs from the fungus Cryptococcus neoformans. With bioinformatics and Northern blotting approaches, we found that these miRNAs and their hairpin precursors were present in this fungus. The size of miR1 and miR2 is 22 nt and 18 nt, respectively. The precursors are about ∼70 nt in length that is close to mammalian pre-miRNAs. Characteristic features of miRNAs are also found in miR1/2. We demonstrated that the identified miRNAs, miR1 and miR2, caused transgene silencing via the canonical RNAi pathway. Bioinformantics analysis helps to reveal a number of identical sequences of the miR1/2 in transposable elements (TEs) and pseudogenes, prompting us to think that fungal miRNAs might be involved in the regulation of the activity of transposons and the expression of pseudogenes. This study identified functional miRNAs in C. neoformans, and sheds light on the diversity and evolutionary origin of eukaryotic miRNAs.